O potencial de arrecadação do Imposto sobre Serviços de Qualquer Natureza (ISSQN) nas capitais brasileiras no período de 2013 a 2017 - Batista, Jorge Gomes (2020)
The present work investigated the potential of the Tax on Services of Any Nature (ISSQN) in Brazilian capitals, in order to verify whether these cities use all their capacity to collect this very important tax for city halls. Through the temporal evolution of its collection from 2013 to 2017, we sought to measure the degree of fiscal effort across the production frontier (ISSQN), a strategy that is based on stochastic frontier work for the production of companies, but which tax administration can also be applied. For that, data were collected referring to the total monthly ISSQN revenues in the referred period, where the main variables were, in addition to the ISSQN collection, the IPTU collection, the FPM and FUNDEB transfers, the population, GDP per capita and number of tax auditors and active civil servants in each Finance Secretariat. The city of São Paulo reached the first place in the ranking of the fiscal effort to collect the ISSQN in the period surveyed, while the city of Palmas was in last place in the ranking. The results of this work showed that less than 1/3 of the capitals use more than 70% of their collection capacity and more than 2/3 of the capitals still have a long way to go in terms of structuring their tax machine, both in resources human resources, as well as technical and equipment and technological resources.